Stochastic optimization and dynamics: what they are and why they are important for risk management in sovereign institutions 2 - Kreuser, Jérôme L. (Henry Stewart Talks, 2012)
A framework for sovereigns, Why DSP is important to sovereign institutions, Improving risk management for sovereigns, Crises, DSP, and sovereign institutions, Impact of crisis on sovereigns, Anticipating the next crisis, Mapping a migration path from mean-variance to dynamic stochastic programming, Main points to consider for DSP, An example with a sovereign wealth fund implementing momentum and mean-reversion